LEVEL QUALITY OF VISUM ET REPERTUM OF INJURY IN THE LIVING PEOPLE IN THE HAJI GENERAL HOSPITAL MEDAN - MUHAMMAD BENNY HAFIF ALFARO SIANTURI; ABDUL GAFAR PARINDURI (LP2MTBM MAKARIOZ, 2022)
Visum et Repertum is one of a help that frequently requested by investigator (police) to the doctor regarding injuries to the human body. Visum et Repertum is an evidance tool used in judicial process which not only qualify by the standart writing of medical records, but also have to meet the things that aare required in the judicial system. WHO estimate that for every one death from traffic accident, there are 20 other people who suffer the consequences. To determine the quality level of the aVisum et Repertum of injuries in people at the General Hospital of Haji Medan. The type of this reasearch was descriptive with a retrospective approach. Based on gender of patients who did a Visum et Repertum at the General Hospital of Haji Medan, there were more male patients, amount 109 patients (72,3%), and female patients as many as 41 patients (23,3%). of the 31 – 40 age group the highest number was 50 patients (33,3%).Based on the most scoring results, namely moderate scores with frequency of 120 patients (80%). It was found that male are the largest gender that took Visum et Repertum, with age range of 31 – 40 years old, with Viusm et Repertum in a moderate score.